The concept and measurement of violence against women and men - Walby, Sylvia (Policy Press, 2017)
Available Open Access under CC-BY-NC licence. The extent of violence against women is currently hidden. How should violence be measured? How should research and new ways of thinking about violence improve its measurement? Could improved measurement change policy? The book is a guide to how the measurement of violence can be best achieved. It shows how to make femicide, rape, domestic violence, and FGM visible in official statistics. It offers practical guidance on definitions, indicators and coordination mechanisms. It reflects on theoretical debates on 'what is gender', 'what is violence', and 'the concept of coercive control'. and introduces the concept of 'gender saturated context'. Analysing the socially constructed nature of statistics and the links between knowledge and power, it sets new standards and guidelines to influence the measurement of violence in the coming decades.